Friday

March 27, 2015

March 27, 2015

Posted by **babygirl** on Tuesday, September 6, 2011 at 10:50pm.

-7/3-5/2x=8+2x

6(-7/3)-(5/2)(6)=6(6)+2x(6)

14x-15=48+12x

14x-12x-15=48+14x-14x

2x-15=48

2x-15+15=48+15

2x=-33

2x/2x=-33/2

x=-33/2

- algebra -
**PsyDAG**, Wednesday, September 7, 2011 at 11:09amAgain, you shifted x term on the left sides from first to third equation.

Please only post your questions once. Repeating posts will not get a quicker response. In addition, it wastes our time looking over reposts that have already been answered in another post. Thank you.

**Answer this Question**

**Related Questions**

algebra - solve the following equation by clearing fractions show all work want ...

math - which equation is equivalent to 5x-2(7x+1)=14x? why? a -9x-2=14x b -9xt1=...

math - how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 ...

Maths - find the equation of the perpendicular bisector of the line joining P(2...

Please check Algebra - Please take a look at my work and let me know if I made ...

algebra1 - could you walk-through the steps to solving this problem because I am...

Math - Derivatives - Differentiate the given function. Simplify the answer. f(x...

math - The rectangle given has a perimeter of 14 units. Find the value(s) of x ...

Algebra 1 - 1) what is the simplified form of (x-2)(2x+3)? Use the distributive...

Algebra2 - The area of a square garden in square feet is 49x^2-14x+1. Find the ...